Efektivitas Pajak Hotel dan Restoran Dalam Meningkatkan Pendapatan Asli Daerah (PAD) Kota Medan: Penelitian - Ela Pratiwi; Miftha Rizkina; Yunita Sari Rioni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the effectiveness and contribution of Hotel Tax and Restaurant Tax to the increase of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) in Medan City for the 2020–2024 period using a descriptive quantitative method based on secondary data from the Medan City Regional Revenue Agency (Bapenda). The findings show that the effectiveness of Hotel Tax fluctuated, starting from the “quite effective” category in 2020 (80.01%), decreasing to “less effective” in 2021 (69.74%), then gradually increasing until it reached the “effective” category in 2024 (91.03%). Meanwhile, Restaurant Tax demonstrated a more stable trend, with effectiveness increasing from 76.93% in 2020 to 93.27% in 2023, and slightly declining but remaining in the “effective” category in 2024 (92.88%). In terms of contribution to PAD, Restaurant Tax consistently recorded a high contribution, ranging from 11.70% to 16.81%, while Hotel Tax contributed at a low to medium level, between 4.61% and 6.72%. These findings highlight that the restaurant sector plays a more dominant role in supporting PAD growth in Medan City compared to the hotel sector. Therefore, the local government is advised to maintain optimal Restaurant Tax collection performance while increasing Hotel Tax contribution through more effective tax intensification and extensification strategies.